Use of the Delphi technique in pharmacy practice research - Jaam, Myriam; Awaisu, Ahmed; El-Awaisi, Alla; Stewart, Derek; El Hajj, Maguy Saffouh (Research in social and administrative pharmacy, 2022)
Consensus research methods are used in health services research to generate evidence through systematic means of measuring collective agreement and developing consensus from experts of a subject matter. Delphi technique is the most commonly reported consensus research method and is a structured, multistage interaction method to determine consensus using repetitive administration of anonymous questionnaires across two or three rounds. The Delphi technique is increasingly being used in pharmacy practice research. Despite its wide use in the development of statements of policies, guidelines, and performance indicators, there is lack of standardized guidelines and criteria to support the Delphi technique study design, conduct, and reporting, leading to inconsistent approaches and methodological difficulties among researchers. In this themed article, we provide the reader with a collation of best practices and highlight key methodological issues and areas of uncertainty of the Delphi method, especially as it pertains to pharmacy practice research.